LABOR GYMNASTICS X BURSITE: A PROGRAMMED INTERVENTION (Fiep Bulletin - online, 2011)
The occupational illnesses consist of muscular injuries and/or of tendons, fascias, nerves of the superior members, the waist to scapular and the neck, mainly, caused for the incorrect biomechanics use of these structures, Amongst the occupational pathologies, that are related to the repetitive activities, mainly observes it bursitis that are the inflammation of the synovial stock market, characterized for the occurrence of inflammatory processes in bursas, Frequently located in the shoulders and cause regional pain, during the accomplishment of movements as abductor, external rotation and rise of the arms. When the treatment is inadequate, pain radiates region to scapular or arms and generates functional incapacity. Leaving of the estimated one of the necessity of studies that relate the labor gymnastics with the occupational pathologies, a case study was become fulfilled that it corroborates with the benefits gotten from a supervised program of applied labor gymnastics in a carrying volunteer of bursitis in the shoulders. Ahead of this reality, the study it has for objective to verify the impact of a supervised program of physical exercise of labor gymnastics in the treatment of the pathology bursitis. The research if characterized as descriptive, study of case, application of topography questionnaire and intensity of pain, with composed public-target for an individual of the feminine sex, carrying of the pathology bursitis in the shoulders and sedentary. Finally, she was possible in this in case that, to conclude that a work with programmed, dynamic and resisted physical exercises, was positive minimizing the physical points of pain and damages, that had suffered to losses, recouping the mobility and the force of the structures of the shoulders, the volunteer tells.
Keywords: bursitis; health; work